International marketing in rapidly changing environments - Jean, Ruey-Jer Bryan; Chiou, Jyh-Shen; Zou, Shaoming (Advances in international marketing ;, 2013)
Volume 24 of Advances in International Marketing, guest-edited by Professors Jean, Chiou and Zou, considers the impact of major trends in external and internal environments of the firm on international marketing. Major themes include: emerging market firms? innovation, technology-enabled marketing innovation, global account management, knowledge sharing in international alliances, internationalization of small and entrepreneurial firms, export marketing channels, global companies and issues of national culture on consumers? evaluation of MNEs performance and teaching international marketing to students. Papers in part one focus on innovation from emerging markets, including the impact of technological innovation on management innovation in terms of global account management in emerging markets firms and the impact of context on international strategic alliance knowledge transfer and innovation. Part two combines studies with a small- and medium-sized firm perspective and a focus on entrepreneurship. Part 3 looks at export marketing issues, such as sales subsidiaries, foreign channel selection and dependence on export channel co-ordination. Part 4 is devoted to globalization and culture issues, including the dimensions of a global company and the impact of pervasion of national culture on consumers? Evaluation of MNEs performance. Part 5 deals with the effectiveness of alternative teaching methods of international marketing.